Servier's pipeline in oncology: moving from research to patients. (March 2016) - Therasse, Patrick; Abastado, Jean-Pierre
Patrick Therasse and Jean-Pierre Abastado speak to Roshaine Gunawardana, Managing Commissioning Editor: Patrick Therasse is an MD, PhD who has focused his career on drug development in oncology. He is currently the Head of Oncology Development for Servier. Before working for Servier, he worked 8 years for GlaxoSmithKline Vaccines as Vice President, Head of Global Clinical Development for immunotherapeutics. He started his career at the European Organization for Research and Treatment of Cancer (EORTC) as a research fellow and then served as Director of the EORTC Research Center for 11 years. He has worked in all fields of oncology with a long track record of publications mainly in the field of breast cancer and methodological research. He is most well known for developing new Response Criteria In Solid Tumours (RECIST), the reference for response assessment in cancer clinical trials since 2000. His areas of expertise encompass Phase I–III drug development with small molecules or active/passive immunotherapy and translational research. Jean-Pierre Abastado is an immuno-oncologist in charge of the R&D in Oncology at Servier, where he is Director of the Therapeutic Innovation Pole in Oncology. He conducted his professional career between various academic and industrial institutions. He was trained at Ecole Polytechnique (Paris), prepared his PhD on Major Histocompatibility Complex (MHC) at the Pasteur Institute, and made a postdoctoral training at NIH (Bethesda, MD, USA). He studied T-cell activation in the Immunology department of the Pasteur Institute and at the CNRS. He was Vice President, Chief Scientific Officer of IDM-Pharma, a company specialized in cell therapy against cancer. Before joining Servier, he headed the Laboratory of Tumour Immunology within the Singapore Immunology Network (SIgN) where his team studied the tumor immune microenvironment. He has served on the Editorial board of several journals and in the Scientific Advisory Board of several biotech companies. He has authored more than 120 peer-reviewed publications.